Applications of Plasma Technologies to Material Processing - Speranza, Giorgio; Liu, Wei (Chemical engineer); Minati, Luca. (Milton : Chapman and Hall/CRC, 2019)
This book provides a survey of the latest research and developments in plasma technology. In an easy and comprehensive manner, it explores what plasma is and the technologies utilized to produce plasma. It then investigates the main applications and their benefits. Different from other books on the topic that focus on specific aspects of plasma technology, the intention is to provide an introduction to all aspects related to plasma technologies. This book will be an ideal resource for graduate students studying plasma technologies, in addition to researchers in physics, engineering, and materials science Features Accessible and easy to understand Provides simple yet exhaustive explanations of the foundations Explores the latest technologies and is filled with practical applications and case studies
Chapter 4: Concluding RemarksReferences; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Plasma engineering; Materials; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Physics; SCIENCE / Solid State Physics